An autopsy case of fatal repellent air freshener poisoning. Issue 5 (September 2015) - Hitosugi, Masahito; Tsukada, Chie; Yamauchi, Shinobu; Matsushima, Kazumi; Furukawa, Satoshi; Morita, Satomu; Nagai, Toshiaki
Highlights First autopsy case of repellent air freshener poisoning death. Non-ionic surfactant was absorbed into the blood from alimentary tract within one hour of ingestion. Small amounts of non-ionic surfactant can cause death for an aged person. This case enlightens the importance of preventing accidental ingestion of toxic substances.